Does Banking Digitization Reduce Non-Performing Financing in Sharia Commercial Banks? Evidence from Indonesia - Khasanah, Riskiyatul; Azizah, Nur; Pernamawati, Anni Muslimah; Bahtiar, Moh. Ilham Ali; Arumania, Alvia (International Conference on Islamic Economic (ICIE), 2023)
Digitalization in the banking sector has received great urgency and attention in the last few decades because it has been able to provide many conveniences for banks and customers in conducting transactions, this condition has further increased productivity. This increase in productivity describes an increase in income so that Non-performing financing faced by Sharia Commercial Banks in Indonesia can be minimized. Non-performing financing is necessary because a high NPF can disrupt banking operations. This study aims to study and analyze whether digitalization in the economic and banking sectors can reduce Non-performing financing in Sharia Commercial Banks in Indonesia. This research is a positivist study with a quantitative approach which is analyzed using panel regression with dummy variables, with the help of EViews software. This study uses secondary data in the form of banking digitization data, internal factors in Sharia Commercial Banks in Indonesia. This research provides evidence that digitalization that is occurring in the economic and banking sectors, as well as internal and external banking conditions, have made a significant contribution to reducing Non-performing financing in Sharia Commercial Banks in Indonesia.